Analysis of Suspended Sediment Variability in a Large Highly Turbid Estuary Using a 5‐Year‐Long Remotely Sensed Data Archive at High Resolution. Issue 11 (14th November 2019) - Normandin, C.; Lubac, B.; Sottolichio, A.; Frappart, F.; Ygorra, B.; Marieu, V.
Abstract: Spatial variability of surface suspended particulate matter (SPM) concentration in the Gironde estuary and their relationships with environmental forcing are investigated through high spatial resolution multispectral data collected from July 2013 to August 2018 by the Operational Land Imager (Landsat‐8/OLI) and MultiSpectral Instrument (Sentinel‐2/MSI). A principal component analysis using the T‐mode orientation is applied to the discontinuous multiannual time series composed of 41 remotely sensed images. The three first principal components (PC1, PC2, and PC3) explain 65.7% of the total variance. The SPM distribution associated with PC1 and PC2 exhibits a privileged along‐estuary direction of the oscillation modes, while the spatial patterns of PC3 are clearly dominated by lateral oscillations opposing channels and shoals. The main environmental factors affecting the SPM distribution are identified by the analysis of their temporal patterns. The tidal range and the daily river discharge control the spatial patterns of PC1 and PC2, while the tidal cycles and the wind speed are significantly correlated with PC3. Furthermore, the analysis in the along‐estuary and lateral directions shows marked longitudinal and transverse SPM gradients and a strong control of bathymetry on the SPM spatial distribution. For the first time, we highlight that the maxima of surface residual turbidity are located on the shoals regardless of the environmental (tidal and hydrological) conditions. Compared to previous studies, usually based on single‐point in‐water column measurements, these results provide a novel and complementary description of the spatial variability of SPM. They are useful to validate sediment transport numerical models, but also may improve our understanding of suspended sediment dynamics in estuarine systems governed by an estuarine turbidity maximum. Plain Language Summary: Suspended sediments trapped in estuaries form a so‐called estuarine turbidity maximum, which is of primary importance on many levels. By settling through the water column, suspended sediments induce bed sedimentation and changes in estuarine morphology. They also play a key role on water quality. They reduce the water transparency, limiting primary production, and eventually adsorb organic matter, bacteria, and pollutants. This study provides a statistical analysis of surficial suspended sediment concentration in the Gironde estuary, retrieved from 41 high resolution multispectral satellite images acquired between 2013 and 2018. For the first time, recurrent spatial patterns of suspended particles are described, quantified and statistically related to tidal range, daily river discharge, water depth, and wind speed. Results reveal the strong control of bathymetry on the surface concentration and show that maximum surface turbidity signals are located on shoals regardless of environmental conditions. Compared to previous studies, these results provide a novel and complementary description of the spatial variability of suspended particulate matter. Furthermore, they highlight that high resolution images are useful to validate sediment transport numerical models, but also improve understanding of suspended sediment dynamics in estuarine systems governed by an estuarine turbidity maximum. Key Points: Recurrent spatial patterns of suspended particulate matter are described, quantified, and statistically related to environmental forcing Local bathymetry strongly controls the spatial distribution of surface suspended particles in estuaries dominated by a turbidity maximum The maximum surface turbidity signals are identified to be statistically located on shoals regardless of environmental conditions